1986
DOI: 10.1136/gut.27.6.642
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local antibody responses to gastric Campylobacter pyloridis in non-ulcer dyspepsia.

Abstract: SUMMARY Antibody titres to Campylobacter pyloridis in serum and gastric juice were estimated by an enzyme linked immunosorbent assay (ELISA) to whole organisms obtained from bacterial culture in 39 patients with non-ulcer dyspepsia. Whereas 20 of the 21 patients with chronic gastritis had gastric C pyloridis, 17 patients with no C pyloridis had normal histology in the gastric antrum and body. Significantly raised serum IgG and IgA antibody titres to C pyloridis were found in colonised patients with gastritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
9

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(108 citation statements)
references
References 15 publications
3
96
0
9
Order By: Relevance
“…1 H. pylori-specific IgA and IgG can regularly be detected both systemically [2][3][4] and at the gastric mucosal level 3,4 in infected patients, whereas only some patients with chronic gastritis have IgA antibodies (and low levels of IgM antibodies) in their gastric juice. 3,4 Importantly, despite induction of local immune responses, subsequently treated patients appear to be unprotected against reinfection. 5 Nevertheless, a role for secretory immunity in early H. pylori colonization has been suggested because sucklings are temporarily protected by specific IgA antibodies present in breast milk.…”
mentioning
confidence: 99%
“…1 H. pylori-specific IgA and IgG can regularly be detected both systemically [2][3][4] and at the gastric mucosal level 3,4 in infected patients, whereas only some patients with chronic gastritis have IgA antibodies (and low levels of IgM antibodies) in their gastric juice. 3,4 Importantly, despite induction of local immune responses, subsequently treated patients appear to be unprotected against reinfection. 5 Nevertheless, a role for secretory immunity in early H. pylori colonization has been suggested because sucklings are temporarily protected by specific IgA antibodies present in breast milk.…”
mentioning
confidence: 99%
“…[17][18][19] . Al infectar la mucosa gástrica se produce un aumento local en la síntesis y secreción de citoquinas proinflamatorias como las IL (Interleucinas) 1B, 6, 8, 12, 18 y 23, INF-ƴ (Interferón-ƴ) y TNF-α (Factor de Necrosis Tumoral-α) por parte de varias células, como las células dendríticas, células T, monocitos y neutrófilos, entre otras, en respuesta a moléculas y sustancias secretadas por la bacteria y a la interacción directa con ella [20][21][22][23][24][25] .…”
Section: Metodología De Búsquedaunclassified
“…Both local and systemic antibody responses to the Helicobacter infection have been demonstrated that include IgA, IgM, and IgG istotypes [3,5,6]. H. pylori bacteria reside in the mucus layer covering the gastric epithelium.…”
Section: Introductionmentioning
confidence: 99%